KAJIAN ONLINE BAGI REMAJA - Nurlela Oktaviani; Siti Asiah; Aulia Ayu Rohayah (Al-Ihsan: Journal of Community Development in Islamic Studies, 2022)
The development of science and technology in this millennial era makes it easier for everyone to connect via the internet with smartphones and computers. The da'wah method has changed where da'wah can be done online with a smartphone link. On the other hand, the negative impact of this digital era is the moral decadence and morality of teenagers. One of the basic things that must be understood and done by teenagers is morals towards parents. Many cases of criminal behavior committed by children to their parents and neglect of parents by their children are triggers for this community service. The method used in this community service is counseling or socialization related to morality towards parents. The results of this community service program are adding insight and increasing family ties and brotherhood among the people of the Telaga Pure Village